High-intensity interval training recommendations for combat sports athletes during the COVID-19 pandemic (Revista de Artes Marciales Asiáticas, 2020)
The COVID-19 pandemic has caused governments to establish quarantine and social distancing for the population in order to decrease the contamination peak, factors that have affected the athletes’ preparation. In this context, we developed some high-intensity interval training (HIIT) recommendations for Olympic combat sports athletes that can be performed at home. The HIIT protocols should be added by body mass-based muscle strengthening exercises (similar to technical exercises), with the goal to preserve athletes’ muscle mass and physical fitness. Finally, emergency situations require contingency plans for sport.